2019
DOI: 10.30848/pjb2019-3(23)
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, ecological feature and conservation of a high montane flora of the Shigar valley (Karakorum range) Baltistan region, northern Pakistan

Abstract: This paper presents the results of exploratory investigation on the flora of the Shigar valley, Central Karakorum Mountains, conducted in 2013-2016. The studies completed with the documentation of 345 vascular plants distributed in 206 genera and 63 families with maximum species of flowering plants. Asteraceae and Saussurea were leading taxa in terms of family and genera respectively. Arid mountain slopes was main habitat type sharing maximum species (84) in the native flora. Generally, the sum of species expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The present study revealed that the dried condition of the Bin Dara, Dir, is reflected in its vegetation in the form of stunted growth, small leaf size, sparse distribution, dwarf height, and isolated individuals of plant species that in turn are characteristics of the xerophytic flora. Our findings are also supported by some of the studies from adjacent areas (Abbas et al, 2019;Ahmad et al, 2019;Ahmed et al, 2019;Anwar et al, 2019;Hussain et al, 2019;Kamran et al, 2020;Khan, 2022). Furthermore, biological spectra are used to assess the life form and leaf sizes for better interpretations of the climatic conditions of an ecosystem.…”
Section: Discussionsupporting
confidence: 91%
“…The present study revealed that the dried condition of the Bin Dara, Dir, is reflected in its vegetation in the form of stunted growth, small leaf size, sparse distribution, dwarf height, and isolated individuals of plant species that in turn are characteristics of the xerophytic flora. Our findings are also supported by some of the studies from adjacent areas (Abbas et al, 2019;Ahmad et al, 2019;Ahmed et al, 2019;Anwar et al, 2019;Hussain et al, 2019;Kamran et al, 2020;Khan, 2022). Furthermore, biological spectra are used to assess the life form and leaf sizes for better interpretations of the climatic conditions of an ecosystem.…”
Section: Discussionsupporting
confidence: 91%
“…Genotypes [20]. On the other hand, excessive vigor may be disadvantageous as it results in vegetative growth at the expense of tuberization [23], resulting in lower yields. Breeders, therefore, have to strike a balance between vegetative growth and maximum tuberization.…”
Section: Discussionmentioning
confidence: 99%
“…In constantly changing environmental conditions under the influence of climatic and anthropogenic factors [5,6], it is important to constantly monitor the state of all components of ecosystems. In addition, it is necessary to study the microbial balance of the soil cover as one of the indicator indicators of the stability of ecological systems [7]. The purpose of our study was to ensure the mass accounting of indicators of the ecological state of territories at the level of biogeocenoses, including parameters that are not monitored by departmental observation networks.…”
Section: Introductionmentioning
confidence: 99%